Psychoemotional disturbances in cardiovascular disease patients: treatment issues - G. V. Pogosova (Кардиоваскулярная терапия и профилактика, 2006)
The article is devoted to treatment of psychoemotional disturbances, typical for cardiovascular disease patients: asthenic syndrome, anxiety and depression. Basic principles of their pharmacotherapy in general and cardiology practice are presented.